Beautiful chaos - Garcia, Kami; Stohl, Margaret; Little, Brown and Company (Boston : Little, Brown, 2011)
Swarms of locusts, record-breaking heat, and devastating storms ravage Gatlin as Ethan and Lena struggle to understand and control the impact of Lena's claiming, which is even causing her family members' abilities to dangerously misfire.
"A Beautiful creatures novel"--Jtk.
Sequel to: Beautiful darkness.
Sequel: Beautiful redemption.
630L
Keywords: Paranormal fiction; Psychic ability; Love stories; Weather; Great powers; Dreams; Families; Supernatural; Psychic ability; Love; South Carolina; Love stories; Dust jackets (Bindings)